The Role of Brand Awareness in Mediating the Influence of Promotion Through Social media On Purchase Intention : Study on Coffee Shops “Sekopi” in Denpasar City - Ni Wayan Arum Maha Dharmeitreya; Ni Wayan Sri Suprapti (International Journal of Management Research and Economics, 2024)
The high consumption of coffee and the phenomenon of changes in people's lifestyles support coffee shop business opportunities. "Sekopi" is one of the well-known coffee shops in Denpasar City. The aim of this research is to explain the influence of promotions via social media on purchase intentions with brand awareness as a mediating variable. Data was collected through a survey of 100 coffee lover respondents in Denpasar City who had never purchased products at the "Sekopi" coffee shop. The analysis techniques used are path analysis and Sobel test. The research results show that promotion via social media has a positive and significant effect on purchase intention; promotion via social media has a positive and significant effect on brand awareness; brand awareness has a positive and significant effect on purchase intention; Brand awareness is able to mediate the influence of promotions via social media on purchase intentions. The results of this research have implications for the management of the "Sekopi" coffee outlet that to increase purchasing intentions, consumer brand awareness should be increased by first increasing promotions via social media.